Archangels of funk : episodes from the continuing drama of Cinnamon Jones: scientist, artiste, and hoodoo conjurer - Hairston, Andrea (Tordotcom, 2024)
"The Water Wars have scrambled the world. Flood refugees are on the run. Disrupters and the nostalgia militia roam the roads, wreaking havoc. Invisible Darknet Lords troll the internet, solidifying their power, while Cinnamon, her three Circus-Bots, and two dogs work with a community of farmers, Motor Fairies, and Wheel-Wizards to provide housing, health care, and education for flood refugees. As Cinnamon confronts threats from the Darknet Lords and the nostalgia militia, she must determine how best to honor her elders and her history while building a future for herself and her charges. It's not going to be easy"--